2018
DOI: 10.1089/scd.2017.0135
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Differentiation of Sorted Human Fetal Pancreatic ALDHhiand ALDHhi/CD133+Cells Toward Insulin-Expressing Cells

Abstract: The enzyme aldehyde dehydrogenase (ALDH) is found in developing and multipotent cell populations, and is important for the production and regulation of retinoic acid, which controls β-cell differentiation in the pancreas. The role of ALDH-expressing cells in the formation of endocrine-like cells and co-localization with the putative stem cell marker CD133 has not been examined during human pancreatic development. This study focuses on the co-expression of CD133 on ALDH cells from the human fetal pancreas (18-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…When transplanted into mouse embryos, ALDH br central acinar/terminal duct cells, but not their ALDH dim counterparts, contribute to both exocrine and endocrine lineages in the developing pancreas [48]. It also has been shown that the ALDH br subpopulation of human fetal pancreatic cells contains a heterogeneous population enriched in CD133 + cells and a subset of markers associated with β -cells in the developing human pancreas [49].…”
Section: Aldh As a Marker For Normal Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…When transplanted into mouse embryos, ALDH br central acinar/terminal duct cells, but not their ALDH dim counterparts, contribute to both exocrine and endocrine lineages in the developing pancreas [48]. It also has been shown that the ALDH br subpopulation of human fetal pancreatic cells contains a heterogeneous population enriched in CD133 + cells and a subset of markers associated with β -cells in the developing human pancreas [49].…”
Section: Aldh As a Marker For Normal Stem Cellsmentioning
confidence: 99%
“…Various combinations of markers including ALDH, CD34, CD133, Sca-1, CD44, and integrin α 2 β 1 have been used to identify putative stem cells, as exemplified by ALDH br CD34 + human cardiac atrial stem cells [53, 54], ALDH br CD133 + human fetal pancreatic stem cells [49], ALDH br Sca-1 + murine prostatic stem cells [50], and ALDH br CD44 + human epidermal stem/progenitor cells [52]. It is worth noting that, besides ALDH, other stem cell-associated markers, such as CD133 and CD44, may also play functional roles in stem cells [193, 194].…”
Section: Aldh and Other Stem Cell Markersmentioning
confidence: 99%
“…There is a longstanding debate regarding whether the adult pancreas contains stem or progenitor cells. Several particular cell groups have been proposed as pancreatic progenitor or progenitorlike cells, which have the ability to differentiate into insulinsecreting cells in vitro, including Nestin-positive cells isolated from mouse pancreas (Wei et al, 2012), cells with high aldehyde dehydrogenase enzyme activity sorted from human fetal and adult pancreas (Loomans et al, 2018;Oakie et al, 2018), and P2RY1-and ALK3-positive cells sorted from human pancreatic ducts (Qadir et al, 2018;Qadir et al, 2020). Recently, a new population of Procr + endocrine progenitors was identified from adult mouse islets (Wang et al, 2020).…”
Section: Islet Organoids Derived From Ascs and Other Sourcesmentioning
confidence: 99%
“…The initial characterization of this population indicates the potential of PDX1-/NKX6.1+ cells to generate islet endocrine cells [23]. In vitro expanded islets undergoing de-differentiation have been shown to generate INS+ beta cells on extended culture [43,44], as well as progenitor cells with high aldehyde dehydrogenase activity extracted from the fetal and adult pancreas [45,46]. Additionally, the pancreatic duct serves as a reservoir of a subset of progenitor cells possessing ability to transdifferentiate to beta cells [47,48].…”
Section: Hla Expressionmentioning
confidence: 99%